Fade Into The Bright - Etting, Jessica Koosed; Schwartz, Alyssa Embree (New York : Delacorte Press, 2021)
Abby spends the summer after her senior year of high school--and a life-changing diagnosis--with her aunt on Catalina Island, reconnecting with family, forging a new path, and finding love.
Ages 12 and up.
Keywords: Genetic disorders -- Fiction; Dating (Social customs) -- Fiction; Aunts -- Fiction; Sisters -- Fiction; Santa Catalina Island (Calif.) -- Fiction